The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.2136/sssaj1990.03615995005400060004x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Storm Effects on Macropore Transport of Surface‐Applied Chemicals in No‐Till Soil

Abstract: Previous research has established that macropores can rapidly transmit water through soil. This observation has raised concern that macropores may also promote rapid movement of agricultural chemicals to groundwater. This is a particular concern for no‐till fields where lack of disruption by tillage can lead to the development of extensive macropore systems. In order to investigate the effect of initial rainfall on chemical transport, strontium bromide hexahydrate (SrBr2·6H2O) and atrazine (2‐chloro‐4‐ethylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(92 citation statements)
references
References 0 publications
4
85
1
2
Order By: Relevance
“…-Whilst a prerequisite for estimation of overall contamination potential, in more detail, relatively more precipitation both before and after pesticide application may serve to decrease resultant groundwater concentrations and thus likelihood for detection. Dilution, increased run-off, decreased soil matrix retainment (Shipitalo et al, 1990) and decreased top-soil cracking (Brown et al, 1995) are potential explanations. More and higher-resolution studies of the effects of precipitation on pesticide contamination potential of groundwater in different environments and in relation to actual pesticide use are needed in order to be able to better and more accurately account for the resultant effects in terms of risk assessment of pesticide contamination of groundwater on different scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…-Whilst a prerequisite for estimation of overall contamination potential, in more detail, relatively more precipitation both before and after pesticide application may serve to decrease resultant groundwater concentrations and thus likelihood for detection. Dilution, increased run-off, decreased soil matrix retainment (Shipitalo et al, 1990) and decreased top-soil cracking (Brown et al, 1995) are potential explanations. More and higher-resolution studies of the effects of precipitation on pesticide contamination potential of groundwater in different environments and in relation to actual pesticide use are needed in order to be able to better and more accurately account for the resultant effects in terms of risk assessment of pesticide contamination of groundwater on different scales.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies who have reported relatively less pesticide transport from wet than from dry soils have further suggested increased soil matrix incorporation and retainment in relatively wetter soils (Shipitalo et al, 1990), and increased top-soil cracking allowing for increased downward flow of water and associated solutes during relatively drier periods of time (Brown et al, 1995) as plausible explanations. It could also be the case that increased run-off in relation to greater precipitation amounts could result in decreased groundwater contamination potential.…”
Section: Climate Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…The opposite was observed when studying mobile herbicides' (isoproturon and mecocrop) transfer through a loamy clay soil (Brown et al, 1995a). In a soil column experiment, Shipitalo et al (1990) pointed out the effect on solute (bromide, strontium and atrazine) availability to transfer of slight precipitation occurring prior to heavy rainfall. Laboratory studies have also displayed the variability of pesticide movement depending on the humidity level of the soil (Geissbuhler et al, 1963;Green et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Esse uso intensivo, embora proporcione uma otimização econômica de uso do capital investido pelo produtor, acarreta algumas conseqüências que terminam por causar seqüelas ao meio ambiente, quais sejam: (i) maior quantidade de agro-químicos por hectare ano (ALBUS; KNIGHTON, 1998;NOLDIN et al, 2002), (ii) maior compactação de solo, pelo maior tráfego de máquinas e pelo impacto da gota de irrigação (AHUJA; LEHMAN, 1983;SHIPITALO et al, 1990) com conseqüente aumento no escorrimento superficial e do processo erosivo, (iii) maior incidência de pragas e doenças e seleção de populações de pragas resistentes aos pesticidas, o que aumenta a intensidade de uso dos mesmos, em um ciclo vicioso.…”
Section: Lista De Tabelasunclassified